2018
DOI: 10.4103/aer.aer_183_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of palonosetron, dexamethasone, and palonosetron plus dexamethasone as prophylactic antiemetic and antipruritic drug in patients receiving intrathecal morphine for lower segment cesarean section

Abstract: Background:Intrathecal morphine is commonly used for postcesarean analgesia. Its use is frequently associated with opioid-induced nausea, vomiting, and pruritus. Palonosetron (0.075 mg) combined with dexamethasone (8 mg) is postulated to have an additive effect over each drug alone. The study, therefore, compared the effect of intravenous (i.v.) palonosetron, dexamethasone, and palonosetron with dexamethasone combination in preventing intrathecal morphine-induced postoperative vomiting and pruritus in lower se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…19,55,56,70,71 Palonosetron, a newer 5-HT 3 receptor antagonist with longer duration of action and reduced effect on the QTc, has shown some promising effects in the limited studies into its effect on pruritus to date. [72][73][74] This study along with the George and Wang metaanalyses did not show a dose response relationship with increasing doses of ondansetron. 18,19 Of note, the 3 studies included in this analysis that compared 4 mg vs 8 mg of ondansetron and the study that compared 0.05 mg/kg and 0.1 mg/kg ondansetron all failed to show any dose-dependent response.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…19,55,56,70,71 Palonosetron, a newer 5-HT 3 receptor antagonist with longer duration of action and reduced effect on the QTc, has shown some promising effects in the limited studies into its effect on pruritus to date. [72][73][74] This study along with the George and Wang metaanalyses did not show a dose response relationship with increasing doses of ondansetron. 18,19 Of note, the 3 studies included in this analysis that compared 4 mg vs 8 mg of ondansetron and the study that compared 0.05 mg/kg and 0.1 mg/kg ondansetron all failed to show any dose-dependent response.…”
Section: Discussionmentioning
confidence: 53%
“…19,55,56,70,71 Palonosetron, a newer 5-HT 3 receptor antagonist with longer duration of action and reduced effect on the QTc, has shown some promising effects in the limited studies into its effect on pruritus to date. 72–74…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that palonosetron alone and a combination of palonosetron–dexamethasone were equally effective in the prevention of PONV; however, dexamethasone alone was least effective among the three groups. [ 19 20 ] The combination of palonosetron–dexamethasone was more effective as compared to only palonosetron for reducing PONV after laparoscopic cholecystectomy. [ 21 ] However, in our study, we observed that the combination of palonosetron–dexamethasone did not significantly reduce the incidence of PONV when compared with either drug alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only non-smoking female patients were recruited because this population has a high risk of PONV [1,15]. The impact of body weight on determining the dose of palonosetron has not yet been investigated; therefore, only obese patients were enrolled.…”
Section: Discussionmentioning
confidence: 99%